PENGARUH LINGKUNGAN KERJA NON FISIK DAN KOMUNIKASI TERHADAP KINERJA PEGAWAI RUMAH SAKIT UMUM DAERAH KOTA TANGERANG - Ahmad Tiaz Gozali; Andri Priadi (Al Hasanah Barokah Foundation, 2026)
The purpose of this study was to determine the impact of non-physical work environment and communication on employee performance at Tangerang City Hospital. The method used is quantitative. The sampling technique used the Slovin formula and obtained a sample of 83 respondents. Data analysis used validity test, reliability test, classical assumption test, regression analysis, correlation coefficient, determination coefficient and hypothesis test. The results of this study are that the non-physical work environment has a significant effect on employee performance with the regression equation Y = 15.862 + 0.592X1, a correlation coefficient of 0.622 with a determination coefficient of 38.7% and the hypothesis test obtained t count> t table or (7.153 > 1.990). Communication has a significant effect on employee performance with the regression equation Y = 12.600 + 0.680X2, a correlation coefficient of 0.712 with a determination coefficient of 50.7% and the hypothesis test obtained t count> t table or (9.121 > 1.990). Non- physical work environment and communication simultaneously have a significant effect on employee performance with the regression equation Y = 8.174 + 0.293X1+ 0.505X2. The correlation coefficient value is 0.754 and the determination coefficient is 56.8% while the remaining 43.2% is influenced by other factors. Hypothesis testing obtained the calculated F value > F table or (52.680 > 2.720).